DIFFERENCES IN PLAQUE INDEX BRUSHING WITH A TOOTHBRUSH HAIRY SOFT AND BRUSHING WITH A TOOTBRUSH HAIRY MEDIUM BEING ON GRADE 4 AND 5 STUDENTS AT PUBLIC PRIMARY SCHOOLS 07 AIR CAMAR KECAMATAN PADANG TIMUR TAHUN 2015 - Muhamad Faisal (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
Plaque consists of a thin layer of a variety of microorganism that forms on the tooth surface sometime after the teeth come into contact with saliva. One of the work done in controlling plaque is by brushing your teeth. This study aims to determine the differences in plaque index brushing with a toothbrush hairy soft and brushing with a toothbrush hairy medium. Scope of plaque index, brushing, tootbrush hairy soft and toothbrush hairy medium.Studies using experimental design methods to design one group pretest posttest. Research conducted in public elementary schools 07 Air Camar Kecamatan Padang Timur on 29 to 30 Januari 2014. Samples are 32 people with a sampling technic that judgment sampling. Data collection is done by direct examination on the subject of research using independent t-test.Result of the study showed plaque index before brushing teeth with toothbrush hairy soft has a value of 3.0 to 4,2 and after brushing teeth with tootbrushing hairy soft has a value of 0.2 to 0.8, while the index of plaque before brushing teeth with tootbrush hairy medium being has value 3.1 to4.2 and after brushing teeth with toothbrush hairy medium being has a value of 0.08 to 0.3. results of independent t-test values obtained tH tT which means no significant difference.Conclusion of the study, there were significant differences between brushing with a toothbrush hairy soft and brushing with a toothbrush hairy medium. Advised to pay attention to the sample texture and a bristle brush is recommended to use a tootbrush hairy medium dental hygiene in order get maximum.